Consumer skepticism: A systematic literature review on its effects and future research directions - Khoirina, Marisya Mahdia; Handriana, Tanti; Usman, Indrianawati (International Journal of Innovative Research and Scientific Studies, 2025)
This systematic literature review (SLR) examines the development, effects, and processes of consumer skepticism within the context of consumer behavior, focusing on its cognitive, affective, and behavioral dimensions. A comprehensive search in SCOPUS and Web of Science retrieved 32 empirical studies meeting predefined inclusion criteria following PRISMA 2020 guidelines. The review reveals that consumer skepticism plays a dual role: it promotes critical thinking and informed decision-making but may also cause distrust, emotional discomfort, and lower brand engagement. Often viewed negatively, skepticism serves as a protective mechanism against deceptive marketing, influencing consumer-brand relationships, particularly in the digital market. The findings underscore the need for further research into skepticism’s impact, especially in digital marketing and CSR initiatives. Future studies should explore strategies that balance the protective benefits of skepticism with its potential to undermine consumer trust and engagement.